Home is where the future is: The BrightFocus Foundation consensus panel on dementia care. Issue 1 (20th November 2017) - Samus, Quincy M.; Black, Betty Smith; Bovenkamp, Diane; Buckley, Michael; Callahan, Christopher; Davis, Karen; Gitlin, Laura N.; Hodgson, Nancy; Johnston, Deirdre; Kales, Helen C.; Karel, Michele; Kenney, John Jay; et al.
Abstract: Introduction: A national consensus panel was convened to develop recommendations on future directions for home‐based dementia care (HBDC). Methods: The panel summarized advantages and challenges of shifting to HBDC as the nexus of care and developed consensus‐based recommendations. Results: The panel developed five core recommendations: (1) HBDC should be considered the nexus of new dementia models, from diagnosis to end of life in dementia; (2) new payment models are needed to support HBDC and reward integration of care; (3) a diverse new workforce that spans the care continuum should be prepared urgently; (4) new technologies to promote communication, monitoring/safety, and symptoms management must be tested, integrated, and deployed; and (5) targeted dissemination efforts for HBDC must be employed. Discussion: HBDC represents a promising paradigm shift to improve care for those living with dementia and their family caregivers: these recommendations provide a framework to chart a course forward for HBDC. Highlights: Five core BrightFocus Foundation panel recommendations: Home‐based dementia care should be considered the nexus of new long‐term care models. New payment models are needed to stimulate, reward, and support home care practices. A skilled new workforce spanning long‐term care needs to be developed and equipped. New technologies to promote best practices must be tested, integrated, and deployed. Value propositions and improved public health communication are needed.